Learning about COVID-19: Sources, trustworthiness, and beliefs - Lisa M. Baumgartner; Joanna Ellis; Kris Hollingsworth; Courtney Peebles (Adult Education Research Conference, 2021)
The purpose of this session will be to briefly review our study results concerning participants’ self-directed learning and beliefs about COVID-19. Second, we discuss challenges in educating individuals about COVID-19.
Keywords: COVID-19; critical thinking; social media